Perilaku Kesehatan Reproduksi Pasangan Usia Subur (PUS) Pada Komunitas Samin Di Kabupaten Blora - Sugiharta, Jarot; Suhardono, Suhardono; Prasetyo, Agus (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
ABSTRACTBackground : Reproductive health problems in the community Samin especially couples of childbearing age is still a concern, they generally do not utilize reproductive health care facilities, have not followed the family planning program, do not follow government rules on health care, they are more trusting bewitched by the teachings Saminisme background.Objective : The aim of this study was to describe reproductive health behavior on fertile age couple (PUS) Samin Communities In The District of Blora.Methods : This research is descriptive quantitative and qualitative approaches, the draft through Exploration Research (explanatory research) The research sample comprised a total population of couples of reproductive age (PUS) Samin community in Blora, as many as 130 people. Sample Qualitative 12 people consisting of family (EFA) and 6 community leaders, and 6 health workers who are in the Samin community.The collection of quantitative data with structured interviews, and in-depth interviews for the qualitative data.The quantitative data in the descriptive analysis, while qualitative data analysis with deskrepsi contents.Result : The results showed that 98.5% of respondents are knowledgeable both about the ante natal care, 96.2% of respondents are knowledgeable both about post natal care, 92.3% of respondents good knowledge about family planning. 97.7% of respondents are supportive of the ante natal care, 97.7% of respondents are supportive of the post natal care services, 97.7% of respondents are supportive of the KB and the ante natal care 95.4% of respondents, 92.3% of respondents do post-natal care , 76.2% of respondents planning. Variable knowledge has a very close relationship with a significance value of 0.003 to the magnitude of the possible influence of Odds Ratio (OR) was 14.881 (Exp (B), variable age with a significance value of 0.027 to the magnitude of the possible influence of Odds Ratio (OR) was 10.601 (Exp( B).Conclusion : reproductive health knowledge Samin community largely understand the importance of reproductive health, especially in pregnancy, labor and birth, and yet people still believe Samin once with myths about reproductive health, and so maintain Saminisme cultural customs. For Blora District Health Office, the results of this study can be used as inputs in delivering the program - the EFA program, while for health centers in the region Samin can be input in the improvement of reproductive health care.Keywords: Behavior, Reproductive Health, EFA, Samin